1991
DOI: 10.1111/j.1365-2923.1991.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer literacy among medical, nursing, dental and veterinary undergraduates

Abstract: Universities need to ensure that clinical undergraduates are educated in the use of computers in medical, nursing, dental and veterinary practice. We surveyed 875 students at Glasgow University to determine their computer literacy and attitudes to the use of computers. One in five students had not used a computer during the last year and 16% thought themselves to be a complete novice with computers. Medical students were more likely to have used a computer recently compared to dental and nursing students. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 1 publication
9
31
1
1
Order By: Relevance
“…A five-point scale ranging from no experience to extensive experience was used. Four subscores were developed: hardware (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], software (range 7-35), information access and retrieval (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and dental applications (range 13-65). A total experience score (range 28-140) was constructed by summing all experiential items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A five-point scale ranging from no experience to extensive experience was used. Four subscores were developed: hardware (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], software (range 7-35), information access and retrieval (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and dental applications (range 13-65). A total experience score (range 28-140) was constructed by summing all experiential items.…”
Section: Methodsmentioning
confidence: 99%
“…6 One-third of the students reported not having used a computer in the preceding year. About two-thirds of these students wanted more use of computers in the curriculum.…”
mentioning
confidence: 99%
“…[49101112] Only 5.6% have stated that lack of time is reason for computer illiteracy. It has been observed that, 77.4% students had their own computer and access at home, 18.2% at hostel and only 4.1% goes to cyber café, these results were in accordance to Europe (72%), Jordan (74%), Pakistan (73%), Saudi Arabian (82.74%) and Spain study (76.8%), where students had accessed computers at home.…”
Section: Discussionmentioning
confidence: 99%
“…48 Nevertheless, the need to teach basic computer literacy is increasing. [49][50][51] It has been suggested that specific information on IT should be incorporated into undergraduate curricula, 52 and a course on IT is now recommended for new undergraduates by many universities, including the University of Hong Kong.…”
Section: Knowledgementioning
confidence: 99%